Successful percutaneous balloon occlusion of a large pulmonary arteriovenous malformation. - Duggan, C J (1989)
Percutaneous embolotherapy was carried out successfully in a 79 year old woman with a 56% shunt through a single pulmonary arteriovenous malformation.